A WRITER’S SKILL IN CREATING LANDSCAPE IMAGES (TAMADDUN NURI JURNALI, 2025)
The article presents scientific and theoretical perspectives on the specifics of landscape depiction in Karakalpak prose and the character's perspective. The influence of human character on landscape depiction in Karakalpak literature, as well as the connection between the hero’s perspective and nature, has been analyzed.